Future Interventional Oncology Catheter-Based Therapies - Noda, Christopher Hiro; Roubhaka, Mihail; Charalel, Resmi; Masrani, Abdulrahman; Akinwande, Olaguoke (Digestive Disease Interventions, 2017)
Minimally invasive techniques in the treatment of cancer continue to develop at a rapid pace. Although surgical resection currently remains the only option for a complete cure, not all diseases are amenable to complete removal. This leaves opportunities to develop effective downstaging techniques as well as palliative care. In the realm of minimally invasive oncologic techniques, catheter-based therapies are an attractive option because malignancies require a blood supply to remain active. The intra-arterial (IA) delivery of specific tumoricidal drugs has been shown to be a successful delivery method in a variety of different cancers, and it is currently a progressive area of research. There is work both to increase the delivery specificity of oncologic drugs, including SW43 sigma receptor ligand and nanoparticle research. In addition, oncolytic viral therapy and 3-bromopyruvate have become increasingly more attractive tumoricidal drug prospects. In the future, the success of these therapies will ultimately determine the degree to which IA delivery will compete with the systemic delivery of drugs in the treatment of cancer.
Keywords: oncology; interventional; catheter-based techniques; minimally invasive